Model Perubahan Kadar Air Emping Selama dalam Kemasan Plastik Polipropelin - B. Rahardjo; P. Setyowato; T. Wibowo (agriTECH, 1997)
The objective of this study was to develop a mathematical model for predicting the moisture content of food chips during packaged by permeable plastic film. The mathematical model developed was based on water vapor migration trough permeable film, equilibrium moisture content and mass balances. Samples for the experiment were fried chips made from roasted, pounded flat and dried Gnetum gnemon seeds (emping) found around the city of Yogyakarta. The fried emping chips were packaged using polypropelin plastics. The packages of the fried chips were than stored in glass bottles. The relative humidities of the storage atmosphere inside the bottles were adjusted using salts such that their ranges were between 10% to 90%. The moisture content of the fried emping chips were observed for about twenty (20) days until they reach their equilibrium moisture contents. The results indicate that the model can be used quite well to predict the moisture content of fried chips during packaged in plastic film. However, for dried chip packages stored on atmospheric relative humidity higher than 70% the rate of the moisture content change tends to increase. The range of food moisture content stored under higher atmospheric relative humidity was wider than that stored on atmosphere with lower relative humidity. This wider range of moisture content change makes the model can not predict adequately the equilibrium moisture content by using a single moisture-humidity linear relationship. Estimation of the chip moisture content during storage using two linear relationships was better than that using a single linear relationship.